PELAYANAN CARGO UDARA BERBASIS ONLINE PADA JASA PENGIRIMAN BARANG (STUDI KASUS PADA PT. LANCAR SEMESTA DIRGANTARA) - Susafa’ati Susafa’ati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2016)
Company PT. Lancar Semesta Dirgantara (LSD) is a company that specializes in air freight transport. During these information systems are performed manually only limited information, not to take advantage of the information system website. So that the customer should come directly to the company PT. LSD or by telephone to obtain information about service delivery. The increasing demand for freight services, the more data that must be addressed. Therefore, there are still some obstacles that occur in Company PT. LSD. Besides marketing services company requires delivery of Air Transport in the form of a website to facilitate the customer in obtaining the information. The method used in collecting data and information to support this information system is to perform analysis on the Company's LSD, direct observation, interviews with owners and management companies in the collection and literature data. From the results in the company's research and web-making process, the authors conclude by designing an information system services web-based air transport services (E-Service Air) in order to reduce the constraints faced by customers in obtaining information about the air force service.